PERLINDUNGAN HAK PEKERJA PEREMPUAN MELALUI SERTIFIKASI HAM PERIKANAN YANG BERPERSFEKTIF GENDER - Widyaningrum, Hesti; Rohman, Adi Nur (Jurnal Hukum & Pembangunan, 2021)
Indicators of Human Rights Compliance in Regulations on System and Certification of Human Rights in The Fisheries Sector make Business Actors potentiallyignore The findings of fisheries Human Rights violations that are not included in these indicators, the scopeof indicators of human rights compliance should not be limited also from The findings of Human Rights violations of Fisheries Workers and The method of recovery based on the initiative of The Business Actor as referred to in UNGPs (UN Guiding Principles onBusiness and Human Rights). The narrowness scope, too, has an impact on regulating The Rights Of Women Workers which is not clearly spelled out so that it is also potentially neglected, so that based on The UN Due Diligence for Business Conduct (Guidance)and Women Empowerment Principles from The UN Women and Global Compact can be a reference that indicators are part of Human Rights due diligence must be applied based on a gender perspective where indicators are also elaborated such as covering thepolitical rights of determining gender-based company policies, to the involvement of making progress reports on respecting human rights for women and publicizing them to the community.